Nu is þeo Leore For-Leten: Conventionality, Complexity and Substitution Sets in Historical English Spelling - Stenroos, Merja (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2024)
This paper considers some assumptions about historical English spelling, in particular the idea that historical orthographies, in the absence of standardisation, naturally tend to a close spelling-sound correspondence. It focuses on the group of Early Middle English texts copied by the Tremulous Hand of Worcester in the late twelfth or early thirteenth century, and addresses the question to what extent it is fair to consider them representative of an archaising strategy, a product of antiquarian interest. It is suggested that, while the texts copied by the Tremulous Hand, like most Middle English copied texts, are likely to carry over some features from their exemplars, they reflect a competent use of English as a living written medium and are consistent with other twelfth- and thirteenth-century writing systems. Accordingly, there seems to be no reason to assume a specifically antiquarian motivation behind the Tremulous Hand’s spelling choices. Rather, they reflect three basic features that are present throughout the history of English writing: conventionality, complexity and the use of substitution sets.